2012
DOI: 10.1136/jnnp-2012-302547
|View full text |Cite
|
Sign up to set email alerts
|

Risk of epilepsy after traumatic brain injury: a retrospective population-based cohort study

Abstract: The risk of epilepsy after TBI varied by patient gender, age, latent interval and complexity of TBI. Integrated care for early identification and treatment of post-trauma epilepsy were crucial for TBI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 31 publications
(25 reference statements)
4
71
0
2
Order By: Relevance
“…Fourth, information on the severity of TBI (such as Glasgow coma scale) and hyperlipidemia, which may be associated with the occurrence of depression, was unavailable. Although some studies have indicated that the severity of TBI may relate to the length of intensive care unit stay [40][41][42] or TBI classification into 2 categories based on the ICD-9-CM: mild brain injury (ICD-9-CM 850) and severe brain injury (ICD-9-CM 851-854), 43 the potential limitations of TBI severity definition were still existing. However, some studies 44,45 have indicated that the severity of TBI was not associated with emotional dysfunction in early postsurgery periods.…”
Section: J Clin Psychiatry 77:4 April 2016mentioning
confidence: 99%
“…Fourth, information on the severity of TBI (such as Glasgow coma scale) and hyperlipidemia, which may be associated with the occurrence of depression, was unavailable. Although some studies have indicated that the severity of TBI may relate to the length of intensive care unit stay [40][41][42] or TBI classification into 2 categories based on the ICD-9-CM: mild brain injury (ICD-9-CM 850) and severe brain injury (ICD-9-CM 851-854), 43 the potential limitations of TBI severity definition were still existing. However, some studies 44,45 have indicated that the severity of TBI was not associated with emotional dysfunction in early postsurgery periods.…”
Section: J Clin Psychiatry 77:4 April 2016mentioning
confidence: 99%
“…Severe TBI was defined as brain injury including brain contusion, SDH, epidural haemorrhage subarachnoid haemorrhage and intracranial haemorrhage. According to earlier studies (33,34), we categorized the diagnoses of skull fracture combined with intracerebral hemorrhage (children with both skull fracture and intracerebral hemorrhage diagnostic codes (800-804 and 851-854) conditions, or diagnostic codes include skull fracture with intracranial injury (800.1-800.4, 800.6-800.9, etc.)) into the severe brain injury group.…”
Section: Study Populationmentioning
confidence: 99%
“…According to the International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM), we defined TBI as ICD-9-CM 800, 801, 803, 804, and 850-854, [10][11][12]17 and stroke as ICD-9-CM 430-437. 18 Coexisting medical conditions in this study were defined as hypertensive diseases (ICD-9-CM 401-405), mental disorders (ICD-9-CM 290-319), diabetes (ICD-9-CM 250), pneumonia (ICD-9-CM 480-486), hyperlipidemia (ICD-9-CM 272.0, 272.1, 272.2, and 272.4), liver cirrhosis (ICD-9-CM 571), myocardial infarction (ICD-9-CM 410), and smoking cessation (identified with administration code [case type = 77] in Taiwan's National Health Insurance system).…”
Section: Methodsmentioning
confidence: 99%
“…8 Socioeconomic impacts of disability following TBI are potentially long-term or lifelong, 7,9 and TBI remains a worldwide leading cause of disability and death. [10][11][12] Yi-Chun Chou and Ta-Liang Chen contributed equally to the article.…”
mentioning
confidence: 98%